Estudo do desempenho de filmes de Ti02 como aceptor de elétrons e obtenção de fases puras de nanopartículas de Ti02: anatase e rutila, sintetizado por uma nova rota química - Pereira, Éder Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The high cost in the production of photovoltaic cells is still a problem for the solar energy usage as an electrical power source. In this context, the work studies the feasibility of using titanium dioxide as an electron acceptor in hybrid photovoltaic cells. In this study was used the polyfluorene (PFO) polymer as electron donor. TiO 2 films, electrodeposited at different potentials, were treated thermally to obtain anatase crystallographic phase. The phase evolution was monitored by X-ray diffraction. The results showed that all films had the anatase phase at 600°C, but for higher electrodeposition potential (-1.2 V), it was not possible to detect the presence of any phase. In order to determine the efficiency of electrodeposited TiO 2 films as electron acceptor, fluorescence measurements were performed using laser scanning confocal microscope (LSCM). It was possible to observe that the PFO when used in conjunction with TiO 2 has a lower emission rate as compared to film in the absence of the TiO 2 . This difference shows that the TiO 2 film obtained in this work is acting effectively as an electron acceptor. In this work has also been developed a new synthesis method for obtaining TiO 2 powder. The different crystallographic phases obtained after heat treatment were analyzed by X-ray diffraction. The results showed that the anatase phase was obtained pure at 600°C with a crystallite size of 24 nm and pure rutile phase at 1000°C with a crystallite size of 55 nm. The crystallite size, as well as the stability of the anatase phase was also studied as a function of the concentration of H 2 O 2 in solution. The crystallite size varied from 11 to 35 nm, for concentrations of 0.009 mol/L and 0.138 mol/L H 2 O 2 , respectively. When heat treated at 825°C the sample obtained with lower concentrations of H 2 O 2 and hence smaller crystallite size became completely into rutile phase, however, for the obtained sample with the highest ...

O alto custo na produção de células fotovoltaicas ainda é uma problemática para a utilização da energia solar como fonte de energia elétrica. Neste contexto, o trabalho realizado estuda a viabilidade do uso do dióxido de titânio como aceptor de elétrons em células fotovoltaicas híbridas. Neste estudo foi utilizando o polímero PFO (polidietilfluoreno) como doador de elétrons. Filmes de TiO 2 , eletrodepositados em diferentes potenciais, foram tratados termicamente para se obter a fase cristalográfica anatase. O surgimento desta fase foi monitorado por meio da técnica de difração de raios-X. Os resultados obtidos demonstraram que todos os filmes apresentaram a fase anatase a 600°C, porém para o maior potencial de eletrodeposição (-1,2 V), não foi possível detectar a presença de qualquer fase. No intuito de se determin ar a eficiência dos filmes eletrodepositados de TiO 2 como aceptor de elétrons, foram realizadas medidas de fluorescência utilizando o recurso da microscopia confocal de fluorescência de varredura laser (LSCM). Foi possível observar que o PFO, quando utilizado em conjunto com o TiO 2 , apresenta uma menor taxa de emissão quando comparado com o filme na ausência de TiO 2 . Esta diferença mostra que o filme de TiO 2 obtido neste trabalho está atuando efetivamente como um aceptor de elétrons. Neste trabalho também foi desenvolvido um novo método de síntese para a obtenção de pó de TiO 2 . As diferentes fases cristalográficas obtidas após tratamento térmico foram analisadas por difração de raios -X. Os resultados obtidos mostraram que a fase anatase foi obtida pura em 600°C com um tamanho de cristalito de 24 nm e a fase rutilo pura em 1000°C com um tamanho de cristalito de 55 nm. O tamanho do cristalito, assim como a estabilidade ...
Keywords: Dióxido de titânio; Semicondutores; Sintese inorganica; Celulas fotoeletricas; Titanium dioxide